Carbon monoxide dehydrogenase inhibitor in cell extracts of Pseudomonas carboxydovorans. - Do, Y S (1990)
Extracts of heterotrophically grown cells of Pseudomonas carboxydovorans were found to contain an inhibitor of carbon monoxide dehydrogenase (CO-DH). The inhibitor activity was not detected in CO-autotrophically grown cells. The inhibitor was extremely stable to heat treatment based on the extent of inhibition of CO-DH activity. The extent of inhibition was proportional to the amount of cell extract added to the reaction mixture. The inhibition was independent of a prior incubation period of the extracts with CO-DH. The inhibitor was precipitable with ammonium sulfate, phenol, and trichloroacetic acid. It was passed through benzoylated dialysis tubing and Amicon ultrafiltration membrane YM2. Denaturing and nondenturing polyacrylamide gel electrophoresis of CO-DH inactivated by inhibitor revealed that the mobilities of native enzyme and subunits were identical to those of active CO-DH. The inhibitor-treated CO-DH retained its original antigenic sites and exhibited enzyme activity upon activity staining. The CO-DH inhibitor of P. carboxydovorans was also active on CO-DHs from Pseudomonas carboxydohydrogena, Acinetobacter sp. strain JC1, and Pseudomonas carboxydoflava.